2018
DOI: 10.1038/s41598-018-23335-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhalational Anesthetics Induce Neuronal Protein Aggregation and Affect ER Trafficking

Abstract: Anesthetic agents have been implicated in the causation of neurological and cognitive deficits after surgery, the exacerbation of chronic neurodegenerative disease, and were recently reported to promote the onset of the neurologic respiratory disease Congenital Central Hypoventilation Syndrome (CCHS), related to misfolding of the transcription factor Phox2B. To study how anesthetic agents could affect neuronal function through alterations to protein folding, we created neuronal cell models emulating the graded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
(60 reference statements)
1
7
0
Order By: Relevance
“…A lack of anti-oxidant response proteins in the face of oxidative stress has previously been observed following acute GA exposure, which led to the suggestion that SOD2 may represent a specific anesthesia target 10,29 . Alteration of the mtUPR is consistent with our previously published findings that illustrated how gas anesthetics alter protein folding and induce endoplasmic reticulum stress 36 . Many neurological disorders exhibit intracellular depositions of misfolded protein aggregates, and increases in mtUPR transcriptional regulators is one of the earliest phenotypic changes observed in chronic neurodegenerative diseases 37 .…”
Section: Discussionsupporting
confidence: 92%
“…A lack of anti-oxidant response proteins in the face of oxidative stress has previously been observed following acute GA exposure, which led to the suggestion that SOD2 may represent a specific anesthesia target 10,29 . Alteration of the mtUPR is consistent with our previously published findings that illustrated how gas anesthetics alter protein folding and induce endoplasmic reticulum stress 36 . Many neurological disorders exhibit intracellular depositions of misfolded protein aggregates, and increases in mtUPR transcriptional regulators is one of the earliest phenotypic changes observed in chronic neurodegenerative diseases 37 .…”
Section: Discussionsupporting
confidence: 92%
“…Inhibition of ER stress overactivation contributed to the relief of isoflurane-induced histopathologic changes (61). Moreover, Coghlan et al confirmed that the induction of ER stress by isoflurane (treatment at a dose of 1.1% for 4 h) occurred after the initiation of protein misfolding (62). These results indicate that cytotoxicity of isoflurane is in a dose-dependent way and related to ER stress.…”
Section: Figure 4 |mentioning
confidence: 90%
“…It is worth noting that the in vivo aggregation of PHOX2B protein has not been reported so far, and so the role of aggregates and their toxic effects in CCHS is unclear. In favor of the aggregation theory, there is the finding that anesthetic agents can promote LO-CCHS, by inducing aggregation and mislocalization of PHOX2B variants via the endoplasmic reticulum (ER) unfolded protein response (UPR) ( Basu et al, 2017 ; Coghlan et al, 2018 ).…”
Section: Modeling Cchs: In Vivo and In Vmentioning
confidence: 99%